The strain energy tuning of the shape memory alloy on the post-buckling of composite plates using finite element method - Rasid, Zainudin A. (Trans Tech Publication, Switzerland, 2012)
This paper presents a geometric non-linear finite element model of shape memory alloy composite plates and its source code in order to determine critical loads and to trace post-buckling paths of the composite plates. A numerical study was conducted on symmetric and anti-symmetric angle-ply and cross-ply composite plates. Buckling and post-buckling improvements of composite plates due to the shape memory effect behaviour of shape memory alloy were carried out. The pre-strained shape memory alloy wires were embedded within laminated composite plates so that recovery stress could be induced with the heated wires. The methods of active property tuning and active strain energy tuning were applied to show the various effects of the shape memory alloy on the studied behaviour. The result showed that significant improvements occurred in the critical loads and the post-buckling paths of the symmetric and anti-symmetric angle-ply and the symmetric cross-ply composite plates due to the active strain energy tuning method. In the case of the anti-symmetric cross-ply composite plate where bifurcation point did not exist, the post-buckling path was substantially improved